Cherubism Mice Also Deficient in c‐Fos Exhibit Inflammatory Bone Destruction Executed by Macrophages That Express MMP14 Despite the Absence of TRAP+ Osteoclasts. (2nd November 2017) - Kittaka, Mizuho; Mayahara, Kotoe; Mukai, Tomoyuki; Yoshimoto, Tetsuya; Yoshitaka, Teruhito; Gorski, Jeffrey P; Ueki, Yasuyoshi
ABSTRACT: Currently, it is believed that osteoclasts positive for tartrate‐resistant acid phosphatase (TRAP+) are the exclusive bone‐resorbing cells responsible for focal bone destruction in inflammatory arthritis. Recently, a mouse model of cherubism ( Sh3bp2 KI/KI ) with a homozygous gain‐of‐function mutation in the SH3‐domain binding protein 2 (SH3BP2) was shown to develop auto‐inflammatory joint destruction. Here, we demonstrate that Sh3bp2 KI/KI mice also deficient in the FBJ osteosarcoma oncogene (c‐Fos) still exhibit noticeable bone erosion at the distal tibia even in the absence of osteoclasts at 12 weeks old. Levels of serum collagen I C‐terminal telopeptide (ICTP), a marker of bone resorption generated by matrix metalloproteinases (MMPs), were elevated, whereas levels of serum cross‐linked C‐telopeptide (CTX), another resorption marker produced by cathepsin K, were not increased. Collagenolytic MMP levels were increased in the inflamed joints of the Sh3bp2 KI/KI mice deficient in c‐Fos. Resorption pits contained a large number of F4/80+ macrophages and genetic depletion of macrophages rescued these erosive changes. Importantly, administration of NSC405020, an MMP14 inhibitor targeted to the hemopexin (PEX) domain, suppressed bone erosion in c‐Fos‐deficient Sh3bp2 KI/KI mice. After activation of the NF‐κB pathway, macrophage colony‐stimulating factor (M‐CSF)‐dependent macrophages from c‐Fos‐deficient Sh3bp2 KI/KI mice expressed increased amounts of MMP14 compared with wild‐type macrophages. Interestingly, receptor activator of NF‐κB ligand (RANKL)‐deficient Sh3bp2 KI/KI mice failed to show notable bone erosion, whereas c‐Fos deletion did restore bone erosion to the RANKL‐deficient Sh3bp2 KI/KI mice, suggesting that osteolytic transformation of macrophages requires both loss‐of‐function of c‐Fos and gain‐of‐function of SH3BP2 in this model. These data provide the first genetic evidence that cells other than osteoclasts can cause focal bone destruction in inflammatory bone disease and suggest that MMP14 is a key mediator conferring pathological bone‐resorbing capacity on c‐Fos‐deficient Sh3bp2 KI/KI macrophages. In summary, the paradigm that osteoclasts are the exclusive cells executing inflammatory bone destruction may need to be reevaluated based on our findings with c‐Fos‐deficient cherubism mice lacking osteoclasts. © 2017 American Society for Bone and Mineral Research.